Molecular Identification of Gut Microflora of Bacillus coagulans Supplemented Feed Fed Macrobrachium rosenbergii Post-Larvae Using 16S rRNA - Manjula, S; Bhavan, P Saravana; Udayasuriyan, R; Anitha, D; Kalpana, R; Manjula, T (The International Journal of Biotechnology, 2019)
Probiotics yield numerous health benefits to the host. In this way the probiotic bacterium, Bacillus coagulans has competitively been excluded the pathogenic bacteria, Streptococcus spp., and Klebsiella spp., from the gut of Macrobrachium rosenbergii post-larvae when given through feed (Manjula et al., 2018). The elimination of these two pathogenic bacteria indicated the fact that B. coagulans improved the disease resistance capacity of M. rosenbergii. The present paper deals with 16S rRNA sequence analysis of gut microbial diversity of M. rosenbergii fed with B. coagulans (CFU, 2.28x10-7) supplemented feed, which revealed the presence of B. coagulans (1541 bp), Lactobacillus fermentum (1516 bp), Lactobacillus lactis (1499 bp), Lactobacillus acidophilus (1507 bp), Escherichia coli (1465 bp) and Staphylococcus aureus (1476 bp). The BLAST of these sequences showed almost 100% similarities with the same species retrieved from the NCBI database. The MAS showed 920 identical amino acids residues, 119 similar amino acids residues and 461 variable amino acids sites. The nucleotide sequence divergence and the calculated phylogenetic information clearly discriminate these bacterial species.